Views of an Iberian identity in the post-war world: Cultural heritage and politics as seen by Portuguese artists - de Oliveira, Leonor (Arte, Individuo y Sociedad, 2020)
Portugal and Spain never shared such a distinctive place in recent European history than in the post-war period. Despite the end of the Second World War and the Nazi-fascist defeat, the Iberian dictators, Salazar in Portugal and Franco in Spain, managed to retain their power. This article analyses the creative and theoretical responses of Portuguese artists to the political situation in the Iberian Peninsula taking into particular consideration their approaches to an Iberian identity. It argues that Paula Rego, Barto dos Santos and Ana Hatherly carried out a reinterpretation of cultural and artistic heritage, iconographic memories and historical narratives and, as a result, formulated alternative views of the past and the present that opposed the Iberian dictatorships’ discourses of a glorious, imperialistic legacy that legitimated their ruling. By proposing to look at the references to Spain in Portuguese artists’ work, this article evidences how Portuguese artists sympathized with the political troubles also endured by the Spanish people and singles out a perception of shared cultural traditions between Spain and Portugal. Finally, this article also emphasizes experimental practices and a deliberate eclectic appropriation and reconfiguration of contemporary or historical references that ultimately shaped attitudes of political resistance.